2018
DOI: 10.3389/fnagi.2018.00119
|View full text |Cite
|
Sign up to set email alerts
|

Sophora flavescens Aiton Decreases MPP+-Induced Mitochondrial Dysfunction in SH-SY5Y Cells

Abstract: Sophora flavescens Aiton (SF) has been used to treat various diseases including fever and inflammation in China, South Korea and Japan. Several recent reports have shown that SF has anti-inflammatory and anti-apoptotic effects, indicating that it is a promising candidate for treatment of Parkinson’s disease (PD). We evaluated the protective effect of SF against neurotoxin 1-methyl-4-phenylpyridinium ion (MPP+)-induced mitochondrial dysfunction in SH-SY5Y human neuroblastoma cells, an in vitro PD model. SH-SY5Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 51 publications
3
17
0
Order By: Relevance
“…Sophora species, especially SF and SJ, have been used to prevent aging-associated neurodegenerative disorders such as PD or ischemia/reperfusion in traditional Chinese medicine. Kim et al indicated that SF extract protected against MPP + -induced neurotoxicology in SH-SY5Y neuroblastoma cells [ 17 ]. ST had similar therapeutic applications to these above Sophora species, but there is no related literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sophora species, especially SF and SJ, have been used to prevent aging-associated neurodegenerative disorders such as PD or ischemia/reperfusion in traditional Chinese medicine. Kim et al indicated that SF extract protected against MPP + -induced neurotoxicology in SH-SY5Y neuroblastoma cells [ 17 ]. ST had similar therapeutic applications to these above Sophora species, but there is no related literature.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating reports have shown that the above Sophora medicinal plants have antioxidative, anti-inflammatory, and neuroprotective effects [ 15 , 16 ]. SF extract protected against MPP + -induced and glutamate-induced neurotoxicology in SH-SY5Y neuroblastoma cells and hippocampal cells [ 17 , 18 ]. SF or SJ extracts protected neuronal damage against focal cerebral ischemia in rats [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, recent studies are directed toward outlining the action mechanism of plant extracts and phytochemicals in the prevention and treatment of neurodegenerative diseases. In particular, Lycium chinense Miller , Sophora flavescens Aiton , and Panax ginseng demonstrated neuroprotective effects in rotenone or 1‐methyl‐4‐phenylpyridinium ion‐induced neurotoxicity (Im et al, ; Kim, Jeon, Kim, Koo, & Kim, ; Kim, Lee, et al, ). Betaine present in L. chinense M and sesquiterpenoid from Tussilago farfara also showed similar effects in rotenone and 6‐hydroxydopamine‐induced toxicity in PC‐12 cells, respectively (Im et al, ; Lee, Song, Huh, Oh, & Kim, ).…”
Section: Discussionmentioning
confidence: 99%
“…To contribute PD cell culture model in vitro , 1.5 ml of 1 × 10 5 cells/ml of SH-SY5Y cells were cultured in 12-well plates for approximately 24 h and were then respectively treated with 0.1% dimethyl sulfoxide (Sigma–Adrich, St. Louis, MO, USA) containing 1 μmol/L (μM) rotenone (Sigma–Adrich, St. Louis, MO, USA) for 24 h, 1 mmol/L (mM) 1-methyl-4-phenylpyridinium (MPP + ; Sigma–Adrich, St. Louis, MO, USA) for 24 h or 100 μmol/L (μM) 6-hydroxydopamine (6-OHDA; Sigma–Adrich, St. Louis, MO, USA) for 24 h (Feng et al, 2015 ; Zhang et al, 2017 ; Kim et al, 2018 ) After being digested and washed with phosphate buffer saline, SH-SY5Y cells were subjected to further treatment and analysis. Each experiment was repeated at least three times.…”
Section: Methodsmentioning
confidence: 99%